Bloodline - Iggulden, Conn (Iggulden, Conn. Wars of the Roses., 2016)
"The third beautifully written novel in the War of the Roses series by bestselling author Conn Iggulden. Winter 1461 - Richard Duke of York is dead, his ambitions in ruins, his head spiked on the walls of the city. King Henry VI is still held prisoner. His Lancastrian Queen rides south with an army of victorious northerners, accompanied by painted warriors from the Scottish Highlands. With the death of York, Margaret and her army seem unstoppable. Yet in killing the father, Margaret has unleashed the sons. Edward of March, now Duke of York, proclaims himself England's rightful king. Factions form and tear apart as snow falls. Through blood and treason, through broken men and vengeful women, brother shall confront brother, king shall face king. Two men can always claim a crown. Only one can keep it. "--